Enhanced photocatalytic performance of ternary g-C3N4/UiO-66/Ag3VO4 composite for methylene blue degradation under visible light irradiation - Kalkidan Meskelu; Abi M. Taddesse; Endale Teju; Zewdu Bezu (Results in Chemistry)
A novel Ag3VO4/UiO-66/g-C3N4-based photocatalyst was synthesized using the solvothermal approach and characterized using XRD, SEM, FTIR, PL, and UV–Vis DRS. The photodegradation capacity of each component was tested using aqueous solutions of methylene blue (MB) and real sample solutions. It was found that the ternary composites (g-C3N4/UiO-66/Ag3VO4, 1 wt%, 5 wt%, 10 wt%, and 15 wt% g-C3N4) demonstrated higher degradation efficiency than the single and binary constituents owing to beneficial interactions in the composite, which favor successful interfacial charge transfer and improve photogenerated e--h+ pair separations. The influence of various experimental factors such as pH, initial dye amount, photocatalyst dose, and scavengers on MB degradation was examined. At optimal conditions of pH 6, catalyst load of 60 mg, and initial dye content of 10 ppm, the percent photodegradation of MB under irradiation with visible light (indoor system) was 99.35 %, while in the outdoor system, it was 99.5 % in 240 min. The selected photocatalyst was also applied for the degradation of real sewage sample solution, which was found to be 80.2 % under indoor and 89 % under outdoor experimental undertakings. After five cycles, the potential of the photocatalyst remained substantial, indicating remarkable reusability. The scavenging experiment suggested that the principal active species were found to be superoxide (O2•) and hydroxide radicals (•OH). Thus, the composite g-C3N4/UiO-66/Ag3VO4 could be a promising option for industrial effluent removal applications, particularly in the purification of organic dye-containing wastewater.